THE PECULIARITIES OF THE DEVELOPMENT AND IMPLEMENTATION OF HEALTH INSURANCE IN UKRAINE - Shchur, R.I.; Plets, I.I.; Matskiv , V.V.; Biloshkursky M.V. , M.V.; Marusiak, V.V. (The actual problems of regional economy development, 2021)
The article substantiates the peculiarities of the development and implementation of health insurance in Ukraine. The aim of the article is to solve the problem of insufficient funding in the field of health care, improve the provision of medical services by analyzing global trends and finding the best way to implement national health insurance in Ukraine. In the process of writing the article, methods of observation, analysis, synthesis, comparison and generalization, grouping, statistical comparison were used to study the theoretical and methodological foundations of health insurance development in Ukraine. An abstract-logical method is used for theoretical generalizations and formation of conclusions. The article analyzes the international models of financing the medical sector. It is established that none of the models functions in absolute form and does not perform all the necessary functions and tasks. It is justified that the modern system of health care has its advantages and disadvantages that affect the quality of medical services. An analysis of the market of voluntary health insurance in Ukraine, which is in the process of development, in particular over the past few years, the interest of the population in this area is growing, but still shows a low level of health insurance. The main aspects of the reform of the medical sector, which are quite successful, are described: the system of organization of levels of medical services has been launched. An analysis of health care financing was conducted, which showed non-compliance with the requirements of the Law of Ukraine "On State Financial Guarantees of Medical Care", which lead to insufficient funding and non-receipt by the medical sector of funds provided by this regulation. It is proposed to continue the reform and improve the provision of health services through the introduction of a national health insurance system, which should be based on a hybrid financing approach, which will combine three types of medical financing and cover the entire population in health insurance. For the successful operation of the hybrid model, it is proposed to accumulate the population’s contributions to the National Health Service of Ukraine through the population insurance mechanism under two programs Standard and Increased, which will create a new market for quality medical services.